2015
DOI: 10.1007/s12011-015-0523-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Arsenite and Arsenate in Testicular Histomorphometry and Antioxidants Enzymes Activities in Rats

Abstract: The main source of environmental arsenic exposure in most countries of the world is drinking water in which inorganic forms of arsenic predominate. The present study was aimed to test the impact of two different compounds of inorganic arsenic in histomorphometric and enzymatic parameters in the testes by oral exposition. Adult Wistar male rats were exposed to sodium arsenite and arsenate in drinking water, testing for each chemical form the concentrations of 0.01 and 10 mg/L per 56 days. The animals intoxicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…Although it was not identified significant alterations in the maturation degree of testis among groups, histopathological analysis revealed important alterations in the testis of As1 and As2 animals, being the most prevalent the presence of vacuolization in seminiferous epithelium. These results partially corroborate a previous study with adult animals, which exhibited vacuoles at the base of the epithelium in some seminiferous tubules after treatment with 10 mg L −1 of arsenite sodium or sodium arsenate for 56 days . Vacuolization in seminiferous epithelium is the morphological response of Sertoli cells against various injuries, among them exposure to toxic agents .…”
Section: Discussionsupporting
confidence: 90%
“…Although it was not identified significant alterations in the maturation degree of testis among groups, histopathological analysis revealed important alterations in the testis of As1 and As2 animals, being the most prevalent the presence of vacuolization in seminiferous epithelium. These results partially corroborate a previous study with adult animals, which exhibited vacuoles at the base of the epithelium in some seminiferous tubules after treatment with 10 mg L −1 of arsenite sodium or sodium arsenate for 56 days . Vacuolization in seminiferous epithelium is the morphological response of Sertoli cells against various injuries, among them exposure to toxic agents .…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiological studies have shown that arsenic exposure causes a reduction of sperm quality and erectile dysfunction in men, culminating in infertility (Nie et al ., ; Hsieh et al ., ). Experimental studies using laboratory rodents have reported a negative impact of arsenic (more than 5 mg/L) on testosterone levels (Sarkar et al ., ; Jana et al ., ), sperm quality (Reddy et al ., ; Guvvala et al ., ; Souza et al ., ), antioxidant enzymes activity in the testis (Souza et al ., ), and fertility indexes (Lima et al ., ). In the latter study, authors described that 10 μg/L of arsenic did not drastically impact male fertility in rats after 56 day exposure (Lima et al ., ), but there is no information about its impact when the exposure time is longer than that period.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental period adopted here corresponds to the embryonic period and all intrauterine fetal development of rats,and has been previously used in studies evaluating the effects of prenatal exposure to toxicants in reproductive tract development (Kozul-Horvath et al, 2012;Li et al, 2018). The concentration of arsenic used in this study was based on our previous studies analyzing the effects of arsenic on male reproduction Souza, Marchesi, Domingues de Almeida Lima, et al, 2016), and corresponds to the dose of 1.6 mg/L in humans, based on the normalization for body surface area proposed by Reagan-Shaw, Nihal and Ahmad (2008). This dose, in turn, is faced by humans in the main arsenic-affected areas in the world (Mukherjee et al, 2006).…”
Section: Experimental Designmentioning
confidence: 99%
“…Humans might be exposed to arsenic mainly through the ingestion of contaminated drinking water in which inorganic arsenic forms are predominant (Hughes, Beck, Chen, Lewis, & Thomas, 2011). Several studies showed toxic effects of arsenic on the male reproductive system of adult animals by inducing decreases in epididymal sperm counts, sperm motility, fertility parameters and antioxidant enzyme activities of the testis and epididymis (Guvvala, Sellapan, & Parameswaraiah, 2016;Lima et al, 2018;Souza, Marchesi, Ferraz, Lima, de Oliveira, & Machado-Neves, 2016;Souza, Marchesi, Domingues de Almeida Lima, Ferraz, Santos, da Matta et al, 2016). Several studies showed toxic effects of arsenic on the male reproductive system of adult animals by inducing decreases in epididymal sperm counts, sperm motility, fertility parameters and antioxidant enzyme activities of the testis and epididymis (Guvvala, Sellapan, & Parameswaraiah, 2016;Lima et al, 2018;Souza, Marchesi, Ferraz, Lima, de Oliveira, & Machado-Neves, 2016;Souza, Marchesi, Domingues de Almeida Lima, Ferraz, Santos, da Matta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation